Réponses

  • Utilisateur Brainly
2014-04-19T12:30:44+02:00
Bonjour, 

Résoudre les équations :

- 3x + 7 = 3x - 11
7 + 11 = 3x + 3x
18 = 6x
18/6 = x
3 = x


2(x - 5) = 3x + 5  
2x - 10 = 3x + 5
- 10 - 5 = 3x - 2x
- 15 = x


- 4(3 + x) = 2x - 6
- 12 - 4x = 2x - 6
- 12 + 6 = 2x + 4x
- 6 = 6x
- 1 = x

Bonne journée à toi! :)
  • Utilisateur Brainly
2014-04-19T12:37:49+02:00
Résoudre les équations :
-3x+7 = 3x-11
-3x-3x=-7-11
-6x=-18
x=3

2(x-5) = 3x+5
2x-10=3x+5
-x=10+5
x=-15

-4(3+x) = 2x-6

-12-4x=2x-6
-6x=6
x=-1